Decision Making and Planning in Islamic Educational Leadership - Destriyati; Muhammad Sirozi (al-Afkar, Journal For Islamic Studies, 2025)
Decision making and planning play a strategic role in determining the direction and quality of leadership in all educational institutions, including the Islamic ones. This article analyzes the importance of decision-making and planning as two key components in Islamic educational leadership. The study was conducted with a qualitative approach using a literature study method. Data was collected from various related, relevant, and upto date literatures, including journals and books published in the last ten years. The results of this study indicate that effective decision-making and planning support educational leaders to make priorities and choose the best alternatives in solving problems and improving the quality of education policies and programs. Effective decision making and careful planning provide educational leaders with a strategic framework and structured steps to achieve educational goals. The relationship between effective decision making and careful planning with the achievement of the goal is very important. Good planning guides decision-making, and the right decisions ensure optimal planning. By understanding this concept, educational leaders can create a conducive learning environment and continuously improve the quality of education.